Influence du contexte socio-économique sur la viabilité des entreprises - Duche D. (Aspects économiques de la production aquacole, 1995)
By describing three examples of aquacultural projects in countries surrounding the Mediterranean sea (Greece, Tunisia, Croatia), the importance of the socio-economic context in the viability of a project appears to be one of the key elements on a par with site quality and factors linked to investments, the financial package and the market, which must be taken into account by promoters of new projects. The choice of managers whose responsibility is to ensure the integration of the project into the socio-economic environment, by representing both the company and the investors, is one of the main elements for success and viability in an activity where profit margins have shrunk.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)